2011
DOI: 10.1002/pip.1235
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of band profile around the grain boundary of Cu(InGa)Se2 solar cell material by scanning probe microscopy

Abstract: We performed scanning tunneling spectroscopy on an as‐grown Cu(InGa)Se2 (CIGS) thin film and photo‐assisted Kelvin probe force microscopy on a CIGS solar cell. From these measurements, we estimated the band profile around the grain boundaries (GBs). The results indicate both downward bending of the conduction band edge and broadening of the band gap near GBs. We can therefore conclude that photo‐generated electrons and holes are easily separated by the built‐in field near GBs, and consequently their recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…Again, such consequence will lead to the effective reduction of the recombination rates at the GBs. It should be noted that the grain boundary of Cu(InGa)Se 2 and Cu 2 ZnSnS 4 solar cell materials has broadening or band bending of the band gap, consequently leading to the suppression of the photogenerated charge carriers at the GBs [27][28][29]. Therefore, the benign characteristics of the GBs of perovskites observed from many experimental measurements could be originated from a favorable larger energy bandgap alignment at the GBs, even though the MAPbI x or PbI x formed at the GBs is defective and contains deep trap centers.…”
Section: Resultsmentioning
confidence: 99%
“…Again, such consequence will lead to the effective reduction of the recombination rates at the GBs. It should be noted that the grain boundary of Cu(InGa)Se 2 and Cu 2 ZnSnS 4 solar cell materials has broadening or band bending of the band gap, consequently leading to the suppression of the photogenerated charge carriers at the GBs [27][28][29]. Therefore, the benign characteristics of the GBs of perovskites observed from many experimental measurements could be originated from a favorable larger energy bandgap alignment at the GBs, even though the MAPbI x or PbI x formed at the GBs is defective and contains deep trap centers.…”
Section: Resultsmentioning
confidence: 99%
“…KFM revealed that random GBs have negative influences on solar cell performance compared to those with low R values in polycrystalline Si, 27,28 and that the electron-hole pairs are well separated at GBs in high-efficiency CIGS solar cells. [29][30][31] According to our previous work on the potential variations around the GBs using KFM, 32 the potentials were higher at GBs by approximately 30 meV than those in the BaSi 2 grain interiors in the undoped n-type BaSi 2 films, suppressing the charge carrier recombination at the GBs. This explains the reason why the minority-carrier diffusion length (ca.10 lm) is much longer than the average grain size of undoped n-BaSi 2 (ca.0.2 lm), 8 which is to be an active layer in a BaSi 2 pn junction solar cell.…”
mentioning
confidence: 99%
“…3(b) was taken, both free electrons and free holes would be excited, but the recombination probability in CIGS should be dominated by the number of electrons as the minority carrier, rather than the number of holes, because the CIGS material is a p-type semiconductor. Our previous work [9] based on the P-KFM and scanning tunneling spectroscopy (STS) suggested that downward band bending occurs in both the conduction and valence bands around the grain boundary of CIGS. Because of this band profile, it is expected that photo-generated free electrons accumulate near the grain boundary.…”
Section: Resultsmentioning
confidence: 99%
“…However, typical CIGS materials consist of micro-crystalline structures, which should include many grains and grain boundaries. In order to investigate local behavior of the grain boundaries in the CIGS solar cells, scanning probe methods are very useful, and several attempts, such as scanning tunneling luminescence [4], electro-assisted scanning tunneling microscopy [5], Kelvin probe force microscopy (KFM) [6,7] and photo-assisted KFM (P-KFM) [8,9], have been reported. On the other hand, theoretical studies indicate that Cu vacancies [V Cu ] are easily formed at the grain boundary [10] and that V Cu creates a shallow acceptor level in the bandgap of CIGS [11][12][13].…”
Section: Introductionmentioning
confidence: 99%